Regional cerebellar atrophy related to disability and cognitive progression in multiple sclerosis - Myrte Strik; Iris Dekker; Aurélie Ruet; Hanneke E. Hulst; Mike P. Wattjes; Frederik Barkhof; Bernard M.J. Uitdehaag; Joep Killestein; Menno M. Schoonheim (NeuroImage: Clinical)
Objective: The implications of cerebellar pathology on clinical disease progression in multiple sclerosis (MS) remain unclear. This study investigated regional cerebellar atrophy related to physical disability and cognitive impairment progression. Methods: We included 331 MS patients and 95 controls (Amsterdam MS Cohort, 229 patients and 58 controls re-evaluated after 5 years). Assessments included baseline MRI, and disability and cognition at baseline and follow up. Cerebellar (sub)cortex was parcellated, volumetric data were determined and related to baseline disability and cognition. Longitudinal progression was explored only for regions with significant baseline correlations. Results: At baseline, patients had mild disability (median EDSS 3.0) and 46% showing mild-to-severe cognitive impairment. At follow-up, 34.5% showed EDSS progression and 26.6% cognitive decline. All global and most regional volumes showed atrophy. Cross-sectionally, atrophy of several regions encompassing both anterior and posterior lobes correlated with both disability and cognition, while some correlated with EDSS only. Additionally, cerebellar nuclei only correlated with cognition. Cerebellar volumes were mainly related to information processing speed, working and verbal memory. Longitudinally, atrophy in the posterior lobe, lobule VI and VIIIb, and vermis VI, correlated with cognitive decline, while no variables correlated with disability progression. Conclusion: Regional cerebellar atrophy in both anterior and posterior lobes correlated with disability and cognitive impairment. Posterior regional atrophy was correlated with longitudinal cognitive decline, but none correlated with disability progression. Further research is required to elucidate these relationships.